Conventional adverse features do not predict response to adjuvant chemotherapy in stage II colon cancer. Issue 11 (14th November 2013) - Peng, Sze‐Lin; Thomas, Michelle; Ruszkiewicz, Andrew; Hunter, Andrew; Lawrence, Matthew; Moore, James
Abstract Background The role of adjuvant chemotherapy in patients with stage II colon cancer is unclear. Current guidelines recommend adjuvant chemotherapy for high‐risk patients, although the benefit demonstrated to date is small. Our study examined if adjuvant chemotherapy is associated with improved cancer‐specific survival in high‐risk patients with stage II colon cancer. Methods A retrospective review was performed on patients with stage II (T3‐4N0M0) colon cancer in a multi‐institutional database from 1999 to 2007. Additionally, histology slides were reviewed and cancer‐specific survival data were obtained from the state cancer registry. Adverse features examined were perforation, obstruction, T4 disease, poor differentiation, nodal yield less than 12, lymphovascular invasion and perineural invasion. Survival analysis was performed using the Kaplan–Meier method and Cox regression. Results There were 458 patients in the study, with a median follow‐up of 5.2 years. Four patients (0.8%) were lost to follow‐up. There were 290 (63%) high‐risk patients, defined as having at least one adverse feature. Patients who had adjuvant chemotherapy were significantly younger (median 61 years versus 72 years, P < 0.001) but had comparable ASA score (median 2 versus 2, P = 0.3). There was no significant survival benefit observed associated with any one factor or when grouped. In high‐risk patients the 5‐year cancer specific survival with adjuvant chemotherapy was 84.8% (95% CI 78.7–91.9) compared to surgery alone 92.7% (95% CI 88.5–96.1), P = 0.85). Conclusion Adjuvant chemotherapy did not significantly improve cancer‐specific survival in patients with stage II colon cancer with adverse features. Other markers for selecting appropriate patients for adjuvant treatment are required.